The integration of Acehnese words in Kamus Besar Bahasa Indonesia - Wildan Wildan; Denni Iskandar; Yusri Yusuf; Rahmad Nuthihar; Raiyana Putri Kana (Universitas Syiah Kuala, 2022)
This study aimed to investigate the integration of Acehnese words in Kamus Besar Bahasa Indonesia (KBBI, or Indonesia Dictionary). The contribution of Acehnese words enriches Indonesian vocabulary as the national language. This study followed the descriptive-analytical research method using observational and note-taking techniques. The data source was the online version of KBBI, available on the following web page: https://kbbi.kemdikbud.go.id/. The data comprised the Acehnese vocabulary registered on KBBI and became part of the country's national language. The data analysis used Miles et al.’s (2014) models, consisting of condensation data, display data, and conclusion drawing/verification. The results showed that 134 Acehnese words are integrated into Indonesian. The contribution of the Acehnese language to Indonesian was relatively small compared to the contribution of other local languages. Of 134 Acehnese words, they comprise nouns (70.90%), verbs (21.64%), adjectives (6.72%), and adverbs (0.75%). It was also revealed that the Acehnese words that had been integrated successfully into Indonesian came from 24 areas of use. Based on these findings, it can be concluded that the Acehnese language has enriched the Indonesian vocabulary, and this integration is integral to interlanguage word borrowing. The present study’s findings contribute to the national language digitalization policy, particularly the digitalization of the Indonesian language dictionary, especially to achieve the quality level of the national language dictionary.